The Role of Functional Amyloids in Bacterial Virulence. Issue 20 (12th October 2018) - Van Gerven, Nani; Van der Verren, Sander E.; Reiter, Dirk M.; Remaut, Han
Abstract: Amyloid fibrils are best known as a product of human and animal protein misfolding disorders, where amyloid formation is associated with cytotoxicity and disease. It is now evident that for some proteins, the amyloid state constitutes the native structure and serves a functional role. These functional amyloids are proving widespread in bacteria and fungi, fulfilling diverse functions as structural components in biofilms or spore coats, as toxins and surface-active fibers, as epigenetic material, peptide reservoirs or adhesins mediating binding to and internalization into host cells. In this review, we will focus on the role of functional amyloids in bacterial pathogenesis. The role of functional amyloids as virulence factor is diverse but mostly indirect. Nevertheless, functional amyloid pathways deserve consideration for the acute and long-term effects of the infectious disease process and may form valid antimicrobial targets. Graphical abstract: Highlights: Functional amyloids are widespread in bacteria, pathogenic and non-pathogenic. Bacterial biofilms most commonly function as structural support in the extracellular matrix of biofilms or spore coats, and in cell–cell and cell-surface adherence. The amyloid state can be the sole structured and functional state, or can be facultative, as a secondary state to folded monomeric subunits. Bacterial amyloids can enhance virulence by increasing persistence, cell adherence and invasion, intracellular survival, and pathogen spread by increased environmental survival. Bacterial amyloids may indirectly inflict disease by triggering inflammation, contact phase activation and possibly induce or aggravate human pathological aggregation disorders.